Efektivitas Penggunaan Layanan E-Court pada Perkara Cerai Gugat di Pengadian Agama Cibadak Sukabumi - Abdul Rohman (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2025)
Effectiveness of Using E-Court Services in Divorce Cases at the Cibadak Sukabumi Religious Court", Faculty of Sharia and Law, Department of Ahwal Syakhsiyyah, PTIQ University Jakarta.It is known that the e-Court regulation was motivated by the need for simpler, more affordable, and more efficient judicial services, as stipulated in PERMA No. 7 of 2022, an amendment to PERMA No. 1 of 2019. The research questions are: How is the process of using E-Court services in divorce cases at the Cibadak Religious Court? What is the effectiveness of using E-Court services in divorce cases at the Cibadak Religious Court? And what are the opportunities and obstacles faced in using E-Court services in divorce cases at the Cibadak Religious Court? This study employed a normative empirical research method, employing several approaches: a statute approach, a qualitative descriptive approach, and a sociological approach. Field research data collection techniques were employed, where the research sought data and gathered information from observation, interviews, and documentation. The results of this study conclude that the e-Court process at the Cibadak Religious Court has met the requirements for court effectiveness in litigated divorce cases. This is reflected in the fulfillment of the principles of simpler, faster, and lower-cost justice compared to conventional court proceedings. Through the use of e-Court services, both justice seekers and the court obtain optimal benefits compared to manual litigation mechanisms.